Analisis Penggunaan Aplikasi Majoo Pada Laporan Keuangan Sesuai Sak Emkm Studi Kasus: Umkm Pohara - Sagala, Margaretha Dorlan Olivia; Rahmadi, Rahmadi; Rahmatullah, Marwanto (Publikasi Indonesia, 2025)
Limitations in financial management are often a challenge for MSMEs, especially because of the difficulty in understanding financial conditions and measuring business performance accurately. To overcome this problem, SAK EMKM has been available to help MSMEs in financial management, in addition there are also various free cloud-based accounting applications, such as the Majoo Application, which makes it easier to record finances. This Majoo application has been used by MSME Pohara. This study uses a qualitative descriptive method with a case study approach. Data analysis is carried out through the stages of data reduction, data presentation, verification, and drawing conclusions. The effectiveness of the Majoo Application is measured based on Campbell's Theory which includes 4 (four) indicators, namely: Program Success, Target Success, Satisfaction with the Program, and Overall Goal Achievement. The results of the study show that the Majoo Application is effective in helping MSME financial management based on seven indicators of effectiveness. It is hoped that this study can provide insight for MSMEs that have not used the Majoo Application.